Interpreting and enacting `empowerment` in sport for development: the perspectives of UK stakeholders on a partnership-based programme in Malawi - Annett, E.; Darby, P. (Sport in Society: Cultures, Commerce, Media, Politics, 2024)
This article examines the interpretation and enactment of `empowerment` in a transnational Sport for Development programme that involved a partnership between a UK university and local stakeholders and practitioners in Malawi. In addressing whether the programme was underpinned by a neoliberal or more radical, progressive variant of empowerment, we employed semi-structured interviews with three categories of UK actors: university senior managers; university staff involved in project delivery; and student-volunteers. The findings reveal conflicting perspectives and tensions among these groups. The project staff team sought to promote a radical variant of empowerment through the programme. However, this was constrained by the use of the programme to burnish the University brand in the context of a competitive higher education marketplace and a tendency on the part of student-volunteers to uncritically position themselves as `superior` to Malawian participants and view their involvement in instrumental terms. These perspectives had far reaching implications on relations of power within the programme, the extent to which it functioned on a partnership basis and whose interests were prioritised in its delivery.